Relational ethics and epistemology: The case for complementary first principles in psychology. (April 2021) - Hopner, Veronica; Liu, James H.
In psychology, where a natural science epistemology holds sway, relationships between the researcher and the researched are usually hierarchical and transactional, bound in procedural and legal ethics. This limited view of ethics fails to account for issues of power and privilege, as well as inequalities in economic and sociocultural structures. We argue for a more complete philosophy of science (and practice) consisting of complementary first principles—relational ethics and epistemology. Valuing relational ethics as a first principle means that how knowledge is produced and acted on is complementary in importance with what knowledge is produced. Collaborative relationships grounded in sincerity, reciprocity, and shared purpose become the basis for how psychological knowledge is produced, disseminated, and acted upon. We present two case studies to show how taking action in an ethical manner through relationships formed in the process of doing psychology deepens our conception and practice of psychology as human science.